Structure, Function, and Biosynthetic Origin of Octapeptin Antibiotics Active against Extensively Drug-Resistant Gram-Negative Bacteria. Issue 4 (19th April 2018) - Velkov, Tony; Gallardo-Godoy, Alejandra; Swarbrick, James D.; Blaskovich, Mark. A.T.; Elliott, Alysha G.; Han, Meiling; Thompson, Philip E.; Roberts, Kade D.; Huang, Johnny X.; Becker, Bernd; Butler, Mark S.; Lash, Lawrence H.; et al.
Summary: Resistance to the last-resort antibiotic colistin is now widespread and new therapeutics are urgently required. We report the first in toto chemical synthesis and pre-clinical evaluation of octapeptins, a class of lipopeptides structurally related to colistin. The octapeptin biosynthetic cluster consisted of three non-ribosomal peptide synthetases (OctA, OctB, and OctC) that produced an amphiphilic antibiotic, octapeptin C4, which was shown to bind to and depolarize membranes. While active against multi-drug resistant (MDR) strains in vitro, octapeptin C4 displayed poor in vivo efficacy, most likely due to high plasma protein binding. Nuclear magnetic resonance solution structures, empirical structure-activity and structure-toxicity models were used to design synthetic octapeptins active against MDR and extensively drug-resistant (XDR) bacteria. The scaffold was then subtly altered to reduce plasma protein binding, while maintaining activity against MDR and XDR bacteria. In vivo efficacy was demonstrated in a murine bacteremia model with a colistin-resistant P. aeruginosa clinical isolate. Graphical Abstract: Highlights: In toto chemical synthesis and pre-clinical evaluation of octapeptins Sequencing and analysis of the octapeptin non-ribosomal biosynthetic cluster Structure-activity and structure-toxicity-based design of novel octapeptins Tailoring of the octapeptin structure to optimize exposure and in vivo activity Abstract : Octapeptins are colistin-like lipopeptide antibiotics with activity against multi- and extensively drug-resistant (MDR and XDR) Gram-negative bacteria. We describe the design, synthesis, and early preclinical evaluation of a novel series of octapeptins with superior activity and pharmacokinetics.